Common Law and Civil Law Today - Convergence and Divergence - Novakovic, Marko (Vernon series in law., 2019)
Authors from 13 countries come together in this edited volume, Common Law and Civil Law Today: Convergence and Divergence, to present different aspects of the relationship and intersections between common and civil law. Approaching the relationship between common and civil law from different perspectives and from different fields of law, this book offers an intriguing insight into the similarities, differences and connections between these two major legal traditions. This volume is divided into 3 parts and consists of 22 articles. The first part discusses the common law/civil law dichotomy in the international legal systems and theory. The second focuses on case-law and arbitration, while the third part analyses elements of common and civil law in various legal systems. By offering such a variety of approaches and voices, this book allows the reader to gain an invaluable insight into the historical, comparative and theoretical contexts of this legal dichotomy. From its carefully selected authors to its comprehensive collection of articles, this edited volume is an essential resource for students, researchers and practitioners working or studying within both legal systems.